Central bank communication or the media's interpretation: What moves markets? - Scott Hendry (Bank of Canada, 2012)
The goal of this paper is to investigate what type of information from Bank of Canada communication statements or the market commentary based on these statements has a significant effect on the volatility or level of returns in a short-term interest rate market. Two different text mining methods are used to extract interpretable themes from the document set. Bank FAD press release themes emphasizing the balance of risks, effects on GDP, labour, investment, and the CPI, the terrorist attacks of 2001, and the economic effects of SARS, BSE, blackouts, and other shocks all tended to significantly reduce short-term BAX market volatility. In contrast, discussions of oil prices, the Canadian dollar, the inflation projection and whether the economy is at capacity, and certain forward looking statements significantly increased volatility. Market news stories often offset the effects of the Bank's communication statements and were much more likely to increase market volatility while the Bank reduced it. Market stories were also more likely to have significant effects the greater the difference from the Bank news they covered but could still be important when largely replicating the original information.
Keywords: G14; E58; 330; Financial markets; Asset pricing